GAMBARAN STATUS GIZI PADA PENYEDIAAN MAKANAN (CATERING) DI TK AISYIYAH V KOTA PEKANBARU - Siti Nurfalah Mariyam; Wusono Indarto; Febrialismanto ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Initial observation of the food provided by the manager of catering in TK Aisyiyah V Pekanbaru showed that less than optimal quality of foods that contain nutrients such as proteins whose function is to build and repair the body's cells and produce energy, lack of minerals and vitamins in food play a role in motor development as well as growth and intelligence of children in the care of your body to stay healthy, lack of diversity in school breakfast menus, causing burnout and boredom for children. This study aims to describe the nutritional status of the provision of meals ( catering) in TK Aisyiyah V Pekanbaru. The subjects used in this study are 54 children. The data collection techniques were used that observation. Data analysis techniques by collecting data from observations made on food provided catering management in TK Aisyiyah v cities pekanbaru. The results of the three food samples examined showed that the adequacy of energy, protein, carbohydrates, calcium, phosphorus, and vitamin C did not meet the nutritional needs breakfast for ages 1-3 and 4-6 years. Fat and vitamin A are two samples of foods that meet the nutritional needs and one sample of the food does not meet the nutritional needs for ages 1-3 and 4-6 years. Iron is contained 2 food samples that do not meet the nutritional adequacy and 1 sample meet the nutritional adequacy for ages 1-3 years old and does not meet nutrition for ages 4-6 years. Vitamin B contained 2 samples of food that does not meet nutritional needs and one sample does not meet the nutritional adequacy of food for children aged 1-3 years and meet the nutritional adequacy for ages 4-6 years.Keywords : Nutritional Status, Supply of Food